Kepemimpinan Gembala Jemaat Menurut 2 Timotius 4:1-5 - KALIS STEVANUS (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2021)
Abstract: In today's increasingly complex culture, every institution undergoes changes, and spiritual institutions such as churches are not immune to these changes. The church undergoes a change in its role and context. There is confusion about what a church leader, the pastor of the congregation, should do. There is confusion about how a pastor of the church administers his leadership. This paper aims to describe how leadership in the church should be viewed from a biblical perspective, especially according to 2 Timothy 4:1-5. The author uses a library approach and presents it descriptively. To analyze the text of 2 Timothy 4:1-5, the writer uses the critical historical interpretation method to find the concept of leadership of a church pastor. It was found that the leadership concept of a church pastor is, first: the pastor is a divine appointment and favor; second is that the shepherd must obey in preaching the word; the third is that the pastor of the church must have the courage to state his faults; fourth is the courage to rebuke and advise; fifth is the pastor of the church must be able to control himself in all things; the sixth is that the pastor of the church is required to suffer patiently for the sake of preaching the gospel; the seventh is to be faithful in preaching the gospel; Finally, the pastor of the church needs to complete the ministry task completely. This leadership model is expected to be a material for reflection and learning for leaders in the local church regardless of the church organization.  Keywords: Historical Critical, Local Church, Leadership, Pastor.   Abstrak: Dalam budaya zaman sekarang yang semakin kompleks, setiap lembaga mengalami perubahan, dan lembaga rohani seperti gereja pun tidak kebal terhadap perubahan tersebut. Gereja mengalami perubahan dalam peran dan konteksnya. Ada kebingungan tentang apa yang harus dilakukan oleh seorang pemimpin gereja, yaitu gembala jemaat. Ada kebingungan tentang bagaimana seorang gembala jemaat menyelenggarakan kepemimpinannya. Tulisan ini bertujuan untuk mendeskripsikan bagaimana semestinya kepemimpinan di gereja  dipandang dari perspektif Alkitab khususnya menurut 2 Timotius 4:1-5. Penulis menggunakan pendekatan kepustakaan dan menyajikannya secara deskriptif. Untuk menganalisis teks 2 Timotius 4:1-5, penulis menggunakan metode tafsir historis kritis guna menemukan konsep kepemimpinan seorang gembala jemaat. Ditemukan konsep kepemimpinan seorang gembala jemaat adalah, pertama: gembala jemaat adalah penunjukan dan perkenanan ilahi; kedua adalah gembala harus taat memberitakan firman; ketiga adalah gembala jemaat harus berani menyatakan kesalahan; keempat adalah berani menegur dan menasihati; kelima adalah gembala jemaat harus dapat menguasai diri dalam segala hal; keenam adalah gembala jemaat dituntut sabar menderita demi pemberitaan Injil; ketujuh adalah harus setia memberitakan Injil; terakhir adalah gembala jemaat perlu menyelesaikan tugas pelayanan secara tuntas. Model kepemimpinan ini diharapkan menjadi bahan refleksi dan pembelajaran bagi para pemimpin di gereja lokal apa pun organisasi gerejanya.. Kata-kata Kunci: Gembala jemaat, Gereja Lokal, Historis Kritis, Kepemimpinan